The Swiss Robotic Camp: an innovative nationwide teacher training format in educational robotics - Lucio Negrini; Arianna Marras; Christian Giang (Schweizerische Zeitschrift für Bildungswissenschaften)
The Robotic Camp is a teacher training on educational robotics (ER). The aim, besides instructing teachers on ER, was to create a community allowing them to exchange ideas with colleagues from other regions of Switzerland. In this work, the effectiveness of the camp was evaluated using the "Robotics Interest Questionnaire", an instrument to assess ER knowledge and self-efficacy, interest, collaborative work and problem solving. In addition to the questionnaire, interviews were conducted to explore teachers' ideas, perceptions and evaluations of the camp experience. The results show a positive trend between pre- and post-test in all dimensions involved and a statistically significant difference in the factor of self-efficacy and ER knowledge (p<.001) and in problem solving (p=0.047).